Onde não houver liberdade, urge inventá-la: a arte de protesto em tempos sombrios e o caso do teatro universitário independente de Santa Maria (1968-1974) - Corrêa, Atílio Alencar de Moura (2018)
This dissertation has the political theater practiced by the Independent University Theater (TUI) – a group that has stood out in the cultural scene of the city of Santa Maria, Rio Grande do Sul, from its rupture with the original core, related to the students' organization of the Federal University of Santa Maria (UFSM) – as the central object of the research. The historical cut taken by the survey, which covers the period between 1968 and 1974, is also the one that coincides with the most severe time related to political repression in recent history in Brazil. From the historical experience of TUI, therefore, the signs of a link between the theatrical art produced by the group and the initiatives put in place by the main representatives of the Brazilian political theater, such as Teatro de Arena, Opinião and Oficina, will be sought , also investigating the historical trajectory of the engaged art that precedes the Brazilian experiences operated in the period delimited by the research. Through the reconstitution of part of the history of TUI, the intention is to formulate a historiographical narrative conditioned by the perspective of the social history of culture, in which the artistic production is analyzed in relation to the social life that conditions it.